Resveratrol synthase homologs participate in infection of Nicotiana benthamiana by pathogenic plant viruses and fungi - Meng, Zhuo; Wang, Haijuan; Guo, Guozhi; Miao, Junxia; Liu, Juan; Zhou, Hongyou; Zhao, Mingmin; Dong, Baozhu (Frontiers in Microbiology, 2025)
IntroductionResveratrol synthase (RS) is a key enzyme involved in the synthesis of stilbene and resveratrol. Resveratrol has many biological pharmacological activities that are beneficial to human health including anti-cancer, cardiovascular protection, estrogen regulation, antibacterial, antiviral, and reduction of tissue and organ damage. In plants, RS catalyzes the production of resveratrol, which helps to protect against fungal and bacterial diseases.MethodsWe analyzed RS homologues from peanuts (Arachis hypogaea L.) during infection by plant viruses and fungi. The peanut RS gene was cloned and characterized. The peanut RS gene was cloned into the pEAQ-HT-DEST3 plant binary expression vector and transiently expressed in Nicotiana benthamiana.ResultsSequence analysis of the protein revealed a conserved stilbene synthase activity domain. The protein displayed high phylogenetic identity to RS from A. hypogaea (100%), Vitis vinifera (72.42%), and Polygonum cuspidatum (69.51). The results showed that RS expression in plants significantly contributed to infection by turnip mosaic virus (TuMV) and silghtly contributed to viral infection of tobacco mosaic virus (TMV). However, no significant influence of RS expression on infection by tobacco vein mottling virus (TVMV) was observed. Expression of the RS gene was transiently increased upon fungal infection of Botrytis cinerea in N. benthamiana.DiscussionThis finding suggests that transient expression of the RS gene could significantly contribute to infection by turnip mosaic virus (TuMV) and improve the resistance of N. benthamiana to B. cinerea.